The leap - Tan, Yuan Chong (2016)
The Leap is a 90-min alternate historical sci-fi feature film screenplay revolving around dilemma, responsibilities, romance and appreciation of Singapore’s past success. The script aims to strike a good balance between realism and fantasy providing forth several lesson points to take away for the audience including knowledge about the Macdonald house bombing history of Singapore, appreciation of Singapore’s past and a general guide to the complexities of life decisions. The story uncovers the unpredictability of life phases in an entertaining manner and how the main character takes a leap of faith in various decisions along with different circumstances. The plot ties comprehensively as a loop in timeline with key revelations at the end. It involves notion of time travelling, politics, conflicted interests, trust, friendship and romance.